2016
DOI: 10.3346/jkms.2016.31.3.417
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the CagA Antigen and Serum Levels of Anti-Helicobacter pyloriIgG and IgA in Children

Abstract: We tested correlations between anti-Helicobacter pylori IgG and IgA levels and the urease test, anti-CagA protein antibody, degree of gastritis, and age. In total, 509 children (0–15 years) were enrolled. Subjects were stratified as 0–4 years (n = 132), 5–9 years (n = 274), and 10–15 years (n = 103) and subjected to the urease test, histopathology, ELISA, and western blot using whole-cell lysates of H. pylori strain 51. The positivity rate in the urease test (P = 0.003), the degree of chronic gastritis (P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
12
1
2
Order By: Relevance
“…Nonetheless, it can be assumed that the findings of these 2 tests would not vary, because they exhibit a similar accuracy and a high concurrence rate compared with the Korean H. pylori IgG assay (13). Our study findings can be also supported by a recent study which showed that the serum anti- H. pylori IgG and IgA levels correlate well with the positive findings of the urease test and anti-CagA protein antibody test as well as the degrees of gastritis and H. pylori infiltration (23). …”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, it can be assumed that the findings of these 2 tests would not vary, because they exhibit a similar accuracy and a high concurrence rate compared with the Korean H. pylori IgG assay (13). Our study findings can be also supported by a recent study which showed that the serum anti- H. pylori IgG and IgA levels correlate well with the positive findings of the urease test and anti-CagA protein antibody test as well as the degrees of gastritis and H. pylori infiltration (23). …”
Section: Discussionsupporting
confidence: 89%
“…They demonstrated that the anti‐ H. pylori IgG and IgA antibody titers were higher in the sera of CagA‐positive children regardless of age, while IgG and IgA titers increased with chronic gastritis degree, active gastritis, H. pylori infiltration, RUT grade, and older age. Presence of CagA‐positivity was correlated with a high urease test grade and high anti‐ H. pylori IgG/IgA levels …”
Section: Diagnosismentioning
confidence: 95%
“…More precisely, Seo et al. searched correlations between anti‐ H. pylori IgG and IgA levels and the RUT, anti‐CagA antibodies, degree of gastritis, and age in 509 children stratified by age . They demonstrated that the anti‐ H. pylori IgG and IgA antibody titers were higher in the sera of CagA‐positive children regardless of age, while IgG and IgA titers increased with chronic gastritis degree, active gastritis, H. pylori infiltration, RUT grade, and older age.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations